Keselamatan Kerja Dan Penanganan Peti Kemas Terhadap Kinerja Operasional Pada Perusahaan Pelayaran - Rista Apriyani; M. Riduan; Veronica Veronica (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
Services offered by logistics companies cover shipping expedition and airship expedition as well as warehousing. One of the services is called Moving Storing Location (PLP), and hoarding them at Temporary Storage (TPS). The purpose of this study iss to identify the problem at the regulation of container stacking and  to improve good operational performance during the loading and unloading process and container handling in the stacking yard. This research used 2 methods. The first method was field research with 100 population and 80 samples. The second method employed multiple regression analysis, validity, reliability, F, and T test, and coefficient of determination to analyze the data. Based on the product moment correlation analysis, it is found that r = 0,853. It shows that the level of correlation between these variables is in the strong and moderate category. The inter-variable correlation test (hypothesis testing 1) or tcount resulted in 12,447 > ttable 1,991 whereas the hypothesis testing 2 obtained 13,088 > ttable 1,991. Based on the result, Ho is rejected and Ha iss accepted which means both variables affect occupational safety significantly.